Mikulčice 900 : atlas velkomoravské aglomerace = Mikulčice 900 : atlas of Mikulčice agglomeration - Poláček, Lumír (2021)
"The presented atlas Mikulčice 900 is closely related to the web application Virtual Scientific Model of the Great Moravian Mikulčice (Virtuální vědecký model Velkomoravských Mikulčic) ; the atlas is a supplement, to the application in a book form."–from summary